Pushing nano-aerosol measurements towards a new decade – technical note on the Airmodus particle size magnifier 2.0 - J. Sulo; J. Enroth; A. Pajunoja; J. Vanhanen; K. Lehtipalo; K. Lehtipalo; T. Petäjä; M. Kulmala; M. Kulmala; M. Kulmala (Aerosol Research, 2024)
Accurate measurement of the size distribution of sub-10 nm aerosol particles is still a challenge. Here we introduce a novel version of the Airmodus particle size magnifier (PSM 2.0), which is a condensation-particle-counter-based instrument with a sizing range of 1–12 nm. The extended size range compared to the earlier PSM version enables the direct detection of forming clusters and particles as well as the study of their growth processes without the challenges related to particle charging. It also gives an overlap between the activation size distribution measurements with the PSM and mobility size distribution measurements with conventional mobility particle sizers. We compared the performance of PSM 2.0 to that of a mobility particle size spectrometer, the original A10 particle size magnifier, and a Neutral cluster and Air Ion Spectrometer (NAIS) during field measurements. Also, calibration results were compared against the A10 instrument. The results show that PSM 2.0 is able to activate sub-2 nm clusters and that the concentration and size distribution between 2–12 nm compare well, especially with the NAIS.